How 5th grade students see the Universe - Çetinkaya, Nesibe Firdevs (My University, 2020)
The main points of this article are that in size of the Sun, Earth and Moon and their position relatively and most importantly the shape of the Earth concepts in the students’ mind. Students have some thoughts before they are instructed and some of the them cannot change their way of thinking even, they have been persuaded to the concepts. In this research there are three problem that needs to be answered which are how the 5th grade students define the size and shape of the Sun, the Earth and the Moon and their position relatively to each other, what misconception the students have in terms of the size and shape of the Sun, the Earth and the Moon and their position relatively to each other and how the 5th grade students image the size and shape of the Sun, the Earth and the Moon and their position relatively to each other as three-dimensionally. In method there two section one of them is forced question questionnaire and interview among the students who participate questionnaire. forced-open question had been asked which was adapted by [8] for the shape of the Earth. They which are in 5th grade was consisting of around 78 students. When we look at the results, the terms are mixed. There is still misconception about the shape of the earth. Moreover, the most misconception are encountered in the position of sun, earth and moon. The students have trouble to understand the fact when is not compatible with their daily experiences.

Bu makalenin ana noktaları, Güneş’in Dünya’nın ve Ay’ın şeklinin anlaşılması ve Dünya’nın Güneş’in ve Ay’ın birbirlerine olan konumlarını ve büyüklüklerinin karşılaştırılmasıdır. Çoğunlukla öğrencilerin kafalarında canlanan Dünyanın şekli daha çok araştırmanın ana hattını oluşturmaktadır. Öğrencilere öğretilmeden önce bazı düşünceleri vardır ve bazıları bile düşünme şeklini değiştiremez, yeni kavramlara ikna edilmeleri bu yüzden zordur. Bu araştırmada, 5. sınıf öğrencilerinin Güneş, Dünya ve Ay'ın boyutunu ve şeklini nasıl tanımladıklarını ve birbirlerine göre konumlarını nasıl belirlediklerini, öğrenciler açısından ne anlama geldiklerini belirleyen üç problem vardır. Güneş’in, Dünya’nın ve Ay’ın büyüklüğü ve şekli ve birbirlerine göre pozisyonları ve 5. sınıf öğrencilerinin Güneşin, Dünya'nın ve Ayın boyut ve şeklini ve birbirlerine göre konumlarını üç boyutlu olarak nasıl gördükleri. Buradaki yöntemde, iki bölümden biri yönlendirmeli soru anket formu ve ankete katılan öğrenciler arasından 4 öğrenci ile röportaj yapılmıştır. [8] tarafından Dünya'nın şekli için uyarlanan zorunlu açık uçlu sorular soruldu. 5. sınıftaki öğrenciler yaklaşık 78 öğrenciden oluşur. Sonuçlara baktığımızda terimlerin karışık olduğu gözlemlenmiştir. Dünyanın şekli hakkında hala yanlış bir anlayış vardır. Dahası kavram yanılgılarının en fazla olduğu yer Güneş, Dünya ve Ay pozisyonunda rastlanmıştır. Öğrenciler, en çok kavramları günlük deneyimleri ile uyumlu olmadıklarını zaman anlamakta zorlandıkları gözlemlenmiştir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2020
Keywords: Kavram yanılgısı; Yönlendirici sorulardan oluşmuş anket; Güneş, Dünya ve Ay; Misconception; Forced question questionnaire; Sun, Earth and Moon